Determining the Content of Nutrition and Organoleptic Test of Chips from Jackfruit Seed and Durian seed - Sofiyanita Sofiyanita; Sri Nurhayati (Universitas Negeri Medan, 2018)
The seed of jackfruit and seed of Durian are solid waste and rarely consumed by society. To increase economic value, the seed of jackfruit and the seed of Durian utilized and processed to be new food source and one of them was chips. The study was done in three stages, making the chips from the seed of jackfruit and the seed of Durian, analyzing the content of nutrient and organoleptic test. Analyzing the content of nutrient in the study was the level of protein, fat, water, dust, and carbohydrate and organoleptic test at color, taste, aroma, and texture from chips produced. Based on the results of study that the level of protein, fat, water, dust, carbohydrate and organoleptic test of chips from the seed of jackfruit was 1.1151%, 0.9687%,9,3626%, 43118%, 84.2419%, and the chips from the seed of Durian the level of protein, fat, water, dust, and carbohydrate were 1.0786%, 2.7932%, 8,8043%, 3.4763 and 83.8477%. The chips from the seed of jackfruit and the seed of Durian had high level of carbohydrate. Thus the writer likes the chips form the seed of jackfruit and the seed of Durian. Based on Anova test toward color, taste, aroma, and texture it indicated that there is no the difference between the seed of jackfruit and the seed of Durian.